Optimalisasi Fungsi Lahan Pekarangan pada Permukiman Wilayah Pesisir Melalui Budidaya Tanaman Sayur-Sayuran - Lestari, Nunik; Samsuar, Samsuar; Rahman, Khaidir; Novitasari, Ervi; Hambali, Amiruddin; Sukainah, Andi; Putra, Reski Praja; Mukhlis, Andi Muhammad Akram; Hidayat, Ilman (Departemen Teknologi Pertanian Universitas Hasanuddin, 2022)
The yard is part of the house that is multifunctional and can provide positive benefits and can even support the needs of the family. One of the productive activities in the yard is to cultivate vegetables. However, most of the yards in coastal villages, such as Laikang Village, have not maximized their function and it is difficult to cultivate vegetables. As a solution, a method is needed to support plant cultivation activities in Laikang Village. This service activity aims to provide cultivation training and the manufacture of hydroponic and verticulture installations for groups of housewives in Laikang Village. This community service activity is carried out using the rapid rural appraisal (RRA) and participatory learning and action (PLA) methods, with the stages of activity in the form of presentation of material related to the theme of the activity, demonstration and direct practice by participants, mentoring, and evaluation. From the series of activities, it can be seen that the people of Laikang Village are very enthusiastic and interested in the technology introduced. This is indicated by the high level of participation and activeness of the participants. In addition, there has been a change in the behavior of the Laikang Village community to take advantage of their previously poorly maintained yard, but has now become a productive yard. This vegetable cultivation activity is also still being continued by the participants independently after the training activities, which indirectly indicates the mastery of knowledge and skills, as well as the achievement of the main goals of service activities.